Investigation of the incidence of vitamin B12 deficiency in leukopenia and neutropenia secondary to infection - Sarbay, Hakan (International Journal of Contemporary Pediatrics, 2019)
Background: Infections and nutritional deficiencies are the most common causes of the leucopenia and neutropenia. In this study, we aimed to find the incidence of vitamin B12 deficiency in patients with leukopenia and neutropenia secondary to infection. Methods: Between September 2018 and December 2018, patients who were referred to Diyarbakır Children Hospital’s Pediatric Hematology and Oncology Clinic for leukopenia and/ or neutropenia were thought to develop secondary to infection retrospectively evaluated. Results: Of the 60 patients that evaluated, 23(38.3%) were female and 37(61.7%) were male. The mean age±SD was 4.75±4.5 years. Severe neutropenia was detected in 5(8.3%), moderate neutropenia in 31(51.7%) and mild neutropenia in 17(28.3%) patients. Neutrophil counts were within normal limits in 7(11.7%) patients. When vitamin B12 levels were examined, 17(28.3%) patients had B12 deficiency. Conclusions: Investigation and treatment of vitamin B12 deficiency in patients with leukopenia and neutropenia may shorten the duration of cytopenia and prevent the development of secondary complications.